EFEKTIVITAS EMOTIONAL INTELLIGENCE TRAINING TERHADAP MAHASISWA DI PRESIDENT UNIVERSITY - Iman Permana; Moh Rafli Alif Aghna; Metiya Riska Pangayow; Anak Agung Ayu Mila Raka Prihandini; Ayutia Faras Mita; Kevin Putra Wimartha; Tesalonika Simanjuntak; Razza Ananda Febryant (CV. Denasya Smart Publisher, 2026)
This study has a goal of testing the effectiveness of emotional intelligence training in enhancing emotional intelligence competency among President University students. The Study used a quantitative approach among 20 Students who took part in a training session conducted in a 90-120 minute session. The training involved five aspects of emotional intelligence, namely: self awareness, self regulation, empathy, motivation, and social skills. Data gathering involved using pre test and post test questionnaires, which were processed using a descriptive technique attached to a thematic approach based on the Kirkpatrick Training Evaluation Model. The results of the study showed an increase in emotional intelligence competency in all dimensions measured, proving the efficacy and applicability of conducting emotional intelligence training at a higher education level.